Consumer Brand Engagement and Brand Communications on Destination Brand Equity Maritine Tourism in Indonesia - MANSUR, Suraya; SARAGIH, Nurhayani; SUSILAWATI, Siti; UDUD, Yusiatie; ENDRI, Endri (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
This study aimed to understand the influence of consumer-brand engagement and brand communication on destination brand equity, survey to maritime tourism of Ujung Kulon and Anak Krakatau, Banten. The population chosen in this study is the Instagram followers of Ujung Kulon and Krakatau Banten.The total of the samples are 96 respondents chosen using purposive sampling. This study used inferential statistic tests, which were divided into two: The correlation Test and Linear Regression Test. This study used a correlational survey method Approach. This research used a quantitative approach and a positivist paradigm. The results showed that the use of Instagram is successful in creating destination brand equity because the entertainment and interaction dimension provided a strong effect on the loyalty dimension of the destination brand equity variable. People who are online and following the Instagram account became loyal because the pictures posted gave entertainment value, joy, and relaxation effect. The interaction between the followers and admin of the account of Maritime Tourism of Ujung Kulon and Anak Krakatau, Banten also added the entertainment value. This study provides new contributions regarding the promotion of maritime tourism destinations through theories about brand engagement, brand equity, and brand communication.